Clinical case-based teaching for emergency residents: a student-centered approach in traditional Chinese medicine - Xu Guangxun; Xu Xiangdong; Zhang Hongsheng; Pei Xiaolu; Fan Shengkai; Cao Ying; Qu Zhicheng (Guoji laonian yixue zazhi)
[Objective] To evaluate the effectiveness of the student-centered, case-based teaching method in the standardized training of traditional Chinese medicine (TCM) resident physicians. [Methods] From January to December 2022, 30 resident physicians undergoing emergency department training were randomly selected as the control group and taught by traditional methods. In this approach, designated instructors provided theoretical lessons, practical demonstrations, and guided trainees in completing pre-selected clinical cases independently. Another 30 resident physicians were randomly chosen as the observation group, taught by a student-centered, case-based teaching method. This method emphasized core pathogenesis, progressively integrated textbook content, and connected multidisciplinary knowledge points. After the training, both groups were surveyed to assess their satisfaction with emergency training and their self-evaluation of clinical syndrome differentiation skills. Entrance exam results were also compared between the two groups. [Results] The observation group showed significantly higher satisfaction and self-evaluation scores for syndrome differentiation ability compared to the control group (P<0.05). Additionally, their clinical syndrome differentiation and treatment scores were significantly superior(P<0.05). [Conclusion] The student-centered, case-based teaching method enhances the clinical diagnosis and treatment skills of resident physicians in standardized training programs and increases their overall satisfaction with the training process.